Co‐percolation of carbon nanotubes and silver nanowires at low area densities: Tuning the optoelectrical performance of transparent electrodes. Issue 2 (20th January 2015) - Ackermann, Thomas; Sahakalkan, Serhat; Kolaric, Ivica; Westkämper, Engelbert; Roth, Siegmar
<x xml:space="preserve">Abstract</x> This work addresses the impact of co‐percolating carbon nanotubes within a silver nanowire network with regard to the optoelectrical performance as a transparent electrode. We carried out a comprehensive measurement series and focused on ultra‐transparent electrodes with optical transmission above 95%. We found an immense improvement of the optoelectrical performance for networks near the percolation threshold of the silver nanowires after carbon nanotubes have been added. We were able to decrease the sheet resistance of the silver nanowire networks by a factor of up to 70 after adding carbon nanotubes. We produced transparent electrodes with industrially acceptable sheet resistance at optical transmission of higher than 97%. This work outlines the potential of co‐percolating rod‐like conductors as a network for ultra‐transparent electrodes. Our experimental work confirms theoretical approaches in percolation theory since we systematically evaluated films with high optical transmission. The most transparent films are beyond the descriptiveness with the percolation scaling law. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)